CURRENT STATUS OF KNOWLEDGE AND ATTITUDES REGARDING ANTIBIOTIC USE AMONG PARENTS OF YOUNG CHILDREN AT NAM DINH PEDIATRIC HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: This study describes the current state of knowledge and attitudes regarding antibiotic use among parents of children at Nam Dinh Pediatric Hospital.Methods: This is a cross-sectional descriptive study using a convenient sampling method and a pre-designed toolkit.Results: 77.3% of parents have correct knowledge about the concept of antibiotics; 89.8% of parents know that antibiotics should be taken in full doses even when the child's symptoms have subsided. The percentage of parents with correct knowledge about the consequences of antibiotic misuse ranges from 56.9% to 62.5%. 78.2% of parents know that full doses and duration are necessary to prevent antibiotic resistance. Over 80% of parents have a positive attitude, agreeing that antibiotics are the most effective treatment for bacterial infections and that improper antibiotic use can cause serious problems. Over 60% of parents agree or strongly agree about the dangers of antibiotic side effects.Conclusion: Parents' knowledge and attitudes regarding antibiotic use for children are limited, with 53.2% having adequate knowledge and 49.1% having a positive attitude.
Keywords: Antibiotics, knowledge, attitudes, and parents of young children.